SUFI PSYCHO-PHYSIO-THERAPY (An Empirical-Based Method) - irham, iqbal (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2017)
This paper describes several forms of therapy for spiritual well-being and physical health based on the values of sufism (tasawwuf) and spiritual exercise (riyadhah). The variety of methods contained in these therapeutic forms can be generally found within sufism in theory, but not specifically in practice. These practical experiences is thus part of a âlocal wisdomâ (kearifan lokal) tradition deserving of study and research.Thus far, the therapies have been performed with patients who suffer from physical ailments such as heart disease, cholesterol excess, hypertension, gout, and kidney disorder, as well spiritual illnesses such as obsessive-compulsive disorder, anxiety, and phobias.From the perspective of sufism, these conditions appear because of the sinful actions committed by the sufferers. These sins disturb or trouble the sufferersâ soul, causing it to acquire negative traits, blocking its âlinkâ to God who is the Source of Peace, Happiness, and Well-being (as-Salam). The âfurtherâ a person is from God, the ânearerâ the person is to problems and disease, and vice-versa. To attain physical and spiritual well-being is to become closer to God.In practice, to cure illnesses, the therapies take the following forms: Rasa Ruhani (Spiritual Sensation), Shalat and Thumaâninah (Prayer with Concentration), and Terapi Nafas (Breathing Therapy).